METHYLCYTISINE ALCALOID POTENTIALLY ACTIVE AGAINST DENGUE VIRUS: A MOLECULAR DOCKING STUDY AND ELECTRONIC STRUCTURAL CHARACTERIZATION - Melo Lucio, Francisco Nithael; da Silva, José Elieudo; Marinho, Emanuelle Machado; Da Silva Mendes, Francisco Rogênio; Marinho, Marcia Machado; Marinho, Emmanuel Silva (International Journal of Research -GRANTHAALAYAH, 2020)
Dengue fever is a serious disease acquired from the Aedes aegypti mosquito present in tropical and subtropical regions, deeply impacting the population's quality of life. Its control requires combating the virus, and the use of substances that do not cause damage to the environment is of fundamental importance. The present work was carried out in silico to perform the structural-electronic characterization of the alkaloid Methylcytisine, a tricyclic quinolizidine alkaloid that has insecticidal activities, identifying the molecular boundary orbitals and descriptors of global chemical reactivity and assessing the inhibitory potential of methylcytisine on NS5 methyltransferase enzyme dengue virus, as well as identifying possible biological targets in humans. Methylcytisine was geometrically optimized through semi-empirical quantum calculations with thermodynamically more stable conformation, characterizing its structure (atoms, angles and bonds) and its reactivity descriptors. The analysis of the molecular docking simulations showed that methylcytisine is coupled in the same active site of the NS5 enzyme methyltransferase DENV, very similar to the complexed ligand S-adenosyl-L-homocysteine. The intermolecular interactions found for the complex formed and the distance values of the enzyme residues, indicate that methylcytisine has potential application as a new inhibitor of the dengue virus, however it has a high possibility of interaction with human neuronal acetylcholine receptors.